2020
DOI: 10.20944/preprints202004.0233.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Why Infants Rarely Die of COVID-19 and Morbidity and Mortality Rates Vary by Location: Pneumococcal and Hib Vaccinations as Possible Means to Mitigate Future Pandemics

Abstract: Two conundrums have puzzled COVID-19 investigators: 1) morbidity and mortality is rare among Infants and young children and 2) rates of morbidity and mortality exhibit very large variances across nations, locals and even within cities. These differences correlate with rates of Haemophilus influenzae type B (Hib) and pneumococcal vaccination, which are almost universal among infants and vary widely by geography among adults and the elderly. The higher the rate of vaccination, the lower the COVID-19 morbidity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 64 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Various studies have indicated that some vaccines may protect against symptomatic SARS-CoV-2 infection and death. A very significant inverse correlation has been found between rates of pneumococcal vaccination at both national and local population levels and rates of SARS-CoV-2 infections and death (Root-Bernstein, 2020). No such correlations were found in that study to the tuberculosis vaccine BCG (Bacillus Calmette Guerin), Haemophilus influenzae type B (Hib), diphtheriatetanus-pertussis, measles-mumps-rubella, or poliovirus vaccinations.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…Various studies have indicated that some vaccines may protect against symptomatic SARS-CoV-2 infection and death. A very significant inverse correlation has been found between rates of pneumococcal vaccination at both national and local population levels and rates of SARS-CoV-2 infections and death (Root-Bernstein, 2020). No such correlations were found in that study to the tuberculosis vaccine BCG (Bacillus Calmette Guerin), Haemophilus influenzae type B (Hib), diphtheriatetanus-pertussis, measles-mumps-rubella, or poliovirus vaccinations.…”
Section: Introductionmentioning
confidence: 70%
“…To conclude, there are many reasons to investigate whether pneumococcal, Hib, meningitis and rubella vaccination may protect against SARS-CoV-2 infection or complications. Epidemiologically, a strong inverse association of pneumococcal vaccinations with rates of SARS-CoV-2 rates of disease and death has been documented by two studies (Root-Bernstein, 2020;Pawlowski, et al, 2020). The epidemiological association makes sense in terms of the particular proteins found in pneumococcal vaccines that are identified in this study as being potentially protective.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations